Pengaruh Jenis Kelamin Terhadap Penilaian Kualitas Visual Lanskap Lingkungan Dengan Menggunakan Metode Scenic Beauty Estimation - Putra, Ivan Satriawan; Auliadiningrum, Alma; Agustyahna, Firman; Putra, Ridwansyah Trisnanda; Syahadat, Ray March (Jounal of Enviromental Science Sustainable, 2021)
Background: Scenic Beauty Estimation (SBE) is often used in landscape evaluation of an environment activities. This article aims to examine the influence of sex on perceptions in visual quality assessment. Methods: The method used was SBE analysis and Mann Whitney test using a sample of 46 male respondents and 65 female respondents. Results: The results obtained there are differences in SBE results between male and female respondents. But statistically, this has not differed significantly. Conclusions: Thus it can be concluded that the sample of respondents for SBE analysis does not need to consider sex as long as the desired outcome is not for a certain sex.